2014
DOI: 10.1039/c4ra08823a
|View full text |Cite
|
Sign up to set email alerts
|

Towards high-performance poly(l-lactide)/elastomer blends with tunable interfacial adhesion and matrix crystallization via constructing stereocomplex crystallites at the interface

Abstract: Preparing super-tough and heat-resistant PLLA/elastomer blends by constructing stereocomplex crystallites at the interface to simultaneously tailor interface and matrix properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 51 publications
4
54
0
Order By: Relevance
“…The lowered Tan 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A good interface is quite important to achieve the desired mechanical properties of polymer blends. It is reported that a DCP-induced reactive blending could initiate the in-situ interfacial compatibilization 29,30,[41][42][43] . FT-IR spectra of the residues from DCM-extracted dynamically vulcanized PLA/ENR blends are shown in Figure 8a.…”
Section: Dynamic Mechanical Analysis and The Shape Memory Mechanismmentioning
confidence: 99%
“…The lowered Tan 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A good interface is quite important to achieve the desired mechanical properties of polymer blends. It is reported that a DCP-induced reactive blending could initiate the in-situ interfacial compatibilization 29,30,[41][42][43] . FT-IR spectra of the residues from DCM-extracted dynamically vulcanized PLA/ENR blends are shown in Figure 8a.…”
Section: Dynamic Mechanical Analysis and The Shape Memory Mechanismmentioning
confidence: 99%
“…Other reactive polyethylene copolymers have been used, such as ethylene‐ co ‐methacrylic ionomers , maleic anhydride grafted polyethylene , and ethylene‐ co ‐vinyl alcohol , but EGMA remains the primary method due to rapid kinetics and reasonable cost. PLA has been toughened using a reactive compatibilization system of LLDPE and EGMA, achieving the best toughness with around 20 wt% additives . Evidence of this reaction was demonstrated by Fourier transform infrared (FTIR) spectroscopy, size exclusion chromatography (SEC), 1 H NMR, droplet size, and rheology, leading to improved extension at break (up to 200%) and Charpy impact strength (up to 70 kJ/m 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This led to an impressive 50‐fold increase in Charpy notched impact strength with the incorporation of 20 wt% EMA‐GMA and 0.2 wt% dimethylstearylamine (DMSA) catalyst over neat PLA, and a ∼threefold increase over the analogous uncatalyzed blend . Bai et al also blended EMA‐GMA with PLA in the presence of DMSA catalyst, successfully creating EMA‐g‐PLA with high conversion . Faster, catalyzed reactions may preclude the necessity of high functional polymer loadings or long processing times.…”
Section: Introductionmentioning
confidence: 99%
“…All the blending inevitably results in an undesirable decrease in originally poor heat resistance of PLLA due to the absence of strong heterogeneous nucleating effect of these tougheners on PLLA matrix crystallization. 17,[24][25][26]28,30 Reactive blending is one of the most simple and robust strategy to substantially improve the compatibility of the blends based on the in situ formation of block/gra copolymers at their immiscible interfaces, which can markedly suppress particle coalescence and enhance interfacial adhesion. 12,28,29 Very interestingly, Oyama 12 observed that annealing (at 90 C for 2.5 h) induced PLLA matrix crystallization can not only greatly enhance the heat resistance of PLLA/EGMA blends but also give rise to a notable improvement in the notched impact strength.…”
Section: Introductionmentioning
confidence: 99%